Influência do pré-tratamento com etanol na secagem da polpa do abacate em camada de espuma e sua aplicação em produtos de panificação - Santos, Newton Carlos (2023)
The use of pre-treatments to enhance food drying is effective, ensuring high product quality and energy savings. Foam-mat drying is a versatile and cost-effective technique suitable for producing powdered products. These powders have wide applications in the development of new food formulations. In this context, the present research aims to assess the influence of ethanol pre-treatment on the foam-mat drying of avocado pulp, with the intention of applying the powder in the baking industry. To achieve this, avocado pulp foam was prepared using powdered goat milk (10, 15, and 20%), Emustab® (4, 6, and 8%) with different agitation times (15, 20, and 25 minutes). The foam exhibiting the most suitable physical properties underwent the drying process (at 50, 60, and 70 °C) with or without ethanol pretreatment (99.5%). Empirical and diffusive models were used to describe the drying kinetics and determine the activation energy of the process and thermodynamic properties. The powdered products were characterized in terms of physical-chemical, nutritional, bioactive, antioxidant, morphological, structural, and thermal aspects. Carotenoid stability and water adsorption isotherms were also determined. To assess the potential application of the powder in the baking industry, sandwich bread was prepared using different concentrations of avocado pulp powder (0, 5, 10, 15, 20, and 25%) as a substitute for hydrogenated vegetable fats. In this study, the optimized conditions for avocado pulp foam production were found to be 8% Emustab®, 20% powdered goat milk, and 15 minutes of agitation. The foam drying kinetics were best represented by the Lewis model, particularly when combined with ethanol pretreatment and higher temperatures (70 °C). These conditions also favored several characteristics of the final product, including reductions in water content and activity, an increase in ash and carbohydrates, as well as the content of phenolic compounds and antioxidant activity. Morphological, structural, and thermal analyses revealed irregular, amorphous particles without the formation of new functional groups, which were thermally stable. However, the thermal stability of carotenoids decreased during storage, and water adsorption isotherms displayed a type III curve, with satisfactory estimates using the GAB model. Levels of up to 25% were found to be suitable for replacing hydrogenated fats in bread, resulting in products with lower lipid and carbohydrate contents, higher nutritional value, and increased antioxidant activity, as well as alterations in the structure and color of the bread. In conclusion, this study demonstrated that ethanol pretreatment and foam-mat drying of avocado pulp are effective strategies for producing high-quality powder with wide applications in the development of food formulations.